Financial Inclusion and Financial Literacy among the Millennial Generation: A Bibliometric Study - Judijanto, Loso; Hernat, Okevanrianus Putra (Westscience Press, 2025)
Financial literacy and financial inclusion are critical components of economic empowerment, particularly among the millennial generation, who are actively engaged with digital financial services. This study employs a bibliometric analysis using data exclusively from Scopus and analyzed with VOSviewer to map the intellectual structure, trends, and key research themes in financial literacy and inclusion. The findings reveal that financial literacy is a dominant theme, with strong interconnections to financial behavior, financial knowledge, investment decision-making, and digital finance. The role of social media and fintech innovations is increasingly shaping millennials' financial engagement, highlighting the need for digital financial literacy. Co-authorship analysis identifies three primary research clusters: (1) financial literacy and personal finance, (2) behavioral and methodological frameworks, and (3) technology acceptance in financial behavior. The study underscores the interdisciplinary nature of financial literacy research, incorporating insights from economics, behavioral psychology, and technology adoption models. Implications suggest the need for updated financial education programs integrating investment literacy and digital finance competencies. Future research should explore regional financial inclusion disparities, the role of digital platforms in financial education, and emerging fintech trends influencing millennials' financial behavior.